Rapid assessment of West Nile virus circulation in a German zoo based on honey-baited FTA cards in combination with box gravid traps - Fynmore, Noelle; Lühken, Renke; Maisch, Heike; Risch, Tina; Merz, Sabine; Kliemke, Konstantin; Ziegler, Ute; Schmidt-Chanasit, Jonas; Becker, Norbert (Parasites & vectors, 2021)
For over a decade, monitoring of West Nile virus (WNV) in Germany has consisted of a bird monitoring programme as well as a mosquito-based surveillance programme employing CO2-baited encephalitis vector surveillance (EVS) traps for mass trapping and screening of mosquitoes. In contrast to the EVS traps, the Reiter/Cummings type box gravid trap collects gravid female mosquitoes, which have already taken a blood meal, increasing the likelihood of being infected with pathogens. The traps can be equipped with a honey-baited Flinders Technology Associates® (FTA) card to encourage sugar feeding by the trapped mosquitoes. FTA cards contain nucleic acid preserving substances, which prevent the degradation of viral RNA in the expectorated mosquito saliva and allows for testing the card for flavivirus RNA. This study aimed to assess the suitability of the method for WNV surveillance in Germany as an alternative to previous methods, which are expensive, time-consuming, and predominantly target host-seeking populations less likely to be infected with WNV.